Fabrication of ZrB2 ceramics by reactive hot pressing of ZrB and B. Issue 12 (30th July 2018) - Liu, Limeng; Hou, Zhaoping; Zhao, Yanwei; Geng, Guihong; Wang, Yujin
Abstract: Zirconium diboride (ZrB2 ) ceramics were prepared by reactive hot pressing of ZrB+B powder mixture. Formation of a transient liquid due to eutectic reaction of ZrB2 +Zr→ L eu(ZrB2+Zr) at 1661°C following peritectic decomposition of 2ZrB=ZrB2 +Zr at 1250°C during heating up of the ZrB+B mixture facilitated densification. The liquid phase was subsequently eliminated via reaction of B with Zr in the eutectic liquid L eu(ZrB2+Zr) to result in a dense ZrB2 ceramic. Full density was reached after reactive hot pressing at 1900°C under 30 MPa for 1 h. The ZrB2 ceramic had a refined microstructure consisting of grains of <1.5 μm in size and relatively good Vickers hardness (21 ± 2 GPa) and flexural strength (595 ± 63 MPa).